Antibacterial activity of autochthonous bacteria isolated from Anabas testudineus (Bloch, 1792) and it's in vitro probiotic characterization. (December 2017) - Midhun, Sebastian J.; Neethu, Sahadevan; Vysakh, A.; Sunil, M.A.; Radhakrishnan, E.K.; Jyothis, Mathew
Abstract: Antimicrobial potentials of bacteria isolated from Anabas testudineus have been evaluated through in vitro antagonistic activity against potent fish pathogens. The cellular components and filtered culture medium were effective against six fish pathogens. Altogether 110 strains were isolated from the fish gut, out of which 10 strains were selected through well diffusion method. From them, a strain HGA8B having cumulative maximum score was selected as candidate probiotic. The whole-cell product, heat-killed whole-cell product, Ethyl acetate extract, and the filtered broth were exhibited bactericidal activity against the tested pathogens. In addition, the isolated bacterium was capable of producing extracellular enzymes important for the digestion of food materials and was capable of growth in fish mucus from Oreochromis niloticus . The strain tolerated bile juice secreted by the host and effectively produced biofilm. Analysis of 16S rDNA sequence revealed that isolated strain HGA8B was Bacillus sp. (MF351637). Furthermore, intraperitoneal injection of the bacterium did not induce any pathological signs, symptoms or mortalities in Oreochromis niloticus and revealed the safety of this bacterium as a candidate probiotic in aquaculture. Highlights: Antagonistic activity of cellular components/preparations of strain HGA8B (MF351637) against six potent fish pathogens. Capacity to produce extracellular enzymes viz. amylase, protease, lipase and cellulase were studied qualitatively and quantitatively. Strain HGA8B was capable of growing in fish mucus, tolerated bile juice and produced bio film effectively. Intraperitoneal injection of the bacterium did not induce any pathological signs, symptoms or mortalities in Oreochromis niloticus. By BLAST and phylogenetic analysis strain HGA8B was identified as Bacillus sp. and was showed 99% identity to Bacillus licheniformis.